2013
DOI: 10.1155/2013/987326
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Medicine Injection Shuanghuanglian for Treatment of Acute Upper Respiratory Tract Infection: A Systematic Review of Randomized Controlled Trials

Abstract: Acute upper respiratory tract infections (AURTIs) are the illnesses caused by an acute infection with various viruses and bacteria involving the upper respiratory tract. Shuanghuanglian (SHL) injection, a Chinese medicine intravenous preparation extracted from honeysuckle, Scutellaria baicalensis, and fructus forsythiae, is commonly used to treat AURTIs. Although it is used largely in Chinese hospitals, there is no substantial evidence to demonstrate its clinical effect on AURTIs. We conducted a systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 13 publications
(11 reference statements)
0
32
0
Order By: Relevance
“…A systematic review that evaluated the SHL injection (SHLI) in treating AURTIs concluded that it had potentially reduced the course of disease and relieved some cold symptoms like a fever and coughing (25). However, the poor methodology of the reviewed studies and poor reporting preclude reaching any definite conclusions on its clinical effectiveness.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…A systematic review that evaluated the SHL injection (SHLI) in treating AURTIs concluded that it had potentially reduced the course of disease and relieved some cold symptoms like a fever and coughing (25). However, the poor methodology of the reviewed studies and poor reporting preclude reaching any definite conclusions on its clinical effectiveness.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Clinical trials indicate that the SHLI is more effective than common antibiotics in relieving the symptoms and duration of fever, chest wheezes, cough, sore throat, and nasal congestion in respiratory tract infections [1][2][3][4]. However, SHLI is reported to cause adverse drug reactions (ADRs) in approximately 3.25% of duration of fever, chest wheezes, cough, sore throat, and nasal congestion in respiratory tract infections [1][2][3][4]. However, SHLI is reported to cause adverse drug reactions (ADRs) in approximately 3.25% of patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Shuang‐Huang‐Lian oral liquid (SHL) is a TCMF comprising three herbs: Scutellaria baicalensis , Forsythia suspensa and Lonicera japonica at a ratio of 1:2:1 (Chinese Pharmacopoeia Commission, ). It has been widely used in clinic for the treatment of respiratory diseases, including acute upper respiratory tract infection (Ni, Zhang, Hou, Shi, & Guo, ; Zhang et al, ), acute bronchitis (Ma et al, ) and tonsillitis with significant effect (Cao, Wang, Yu, & Ye, ). Moreover, SHL is the recommended TCMF for treatment of influenza in the Influenza Diagnosis and Treatment Guidelines (2011 edition) in China.…”
Section: Introductionmentioning
confidence: 99%